Perancangan Sistem Informasi Pelayanan Masyarakat Berbasis Web untuk Meningkatkan Efisiensi dan Transparansi di Kantor Desa Teluk Dalem - Amelinda, Putri; Saputra, Emir Fajar; Purnomo, suyitno Adi (LPPM ITBA Dian Cipta Cendikia, 2025)
The development of information technology encourages digital transformation in various sectors, includingpublic services at the village level. Village governments, as basic service providers for the community, arerequired to provide fast, efficient, and transparent services. However, many villages still rely on manualadministrative processes, including Teluk Dalem Village, Mataram Baru Sub-district, East LampungRegency. This research aims to design and implement a web-based community service information systemto improve the quality of village public services. The method used was Research and Development (R&D)with a prototyping approach. Data collection techniques were conducted through observation, interviews,and literature studies. The developed system includes administrative document submission services such asKTP, Family Card, Birth Certificate, SKTM, and Death Letter. The implementation results show anincrease in service efficiency, queue reduction, and increased transparency and accountability of theservice process. This system also supports the achievement of the smart village concept through digitizationof services that are responsive to community needs. This research is expected to become a model fordeveloping village information systems that can be replicated in other areas.